Peran Gaya Kepemimpinan, Kompetensi, dan Kecerdasan Emosional Sangat Penting dalam Membentuk Motivasi dan Kinerja Guru di Madrasah - Wahyu Ramadhan; Muhammad Syahrizal Ibnu Jihad; Abdul Latif Rahman (Moral : Jurnal kajian Pendidikan Islam, 2024)
This study explores the important role of leadership style, competence, and emotional intelligence in shaping teacher motivation and performance in Madrasah. An effective leadership style, solid competence in the field of education, and good emotional intelligence are considered key factors in increasing teacher motivation and performance. This research uses an analytical approach to understand how the interaction between these three elements affects teachers' work environments, as well as their impact on their achievements and professional development. It is hoped that the results of this research will provide deeper insight for Madrasah managers and educational practitioners to improve human resource management and effective staff development strategies.